THE SOCIAL CAPITAL, CORPORATE RESILIENCE AND COMPETITIVENESS DURING PANDEMIC: INDONESIA’S MARINE TRANSPORTATION SERVICES COMPANIES CASE STUDY : - - Eduard Alfian Syamsya Sijabat (Asosiasi Dosen Muda Indonesia, 2023)
Corporate resilience and competitiveness during a pandemic are largely determined by how the company manages its resource capital. This study examined how corporate resilience and competitiveness of marine transportation service companies that rely on social capital with a review point of view from the theory of dynamic capabilities and the resource base-view theory. Using an online method survey with a sample of 446 marine transportation service companies throughout Indonesia. The data were analyzed using multivariate analysis with GSCA application (generalized structured component analysis) and multigroup analysis to examine company age and company size as variable control. The results showed that social capital was associated with corporate resilience and competitiveness as well. The result also showed that corporate resilience was not associated with competitiveness. Meanwhile, in terms of company size, it was associated with a small company. On the contrary, competitiveness was associated with corporate resilience. This study contributes a new empirical finding to the dynamic capability theory and resource base view-based (RBV) competitiveness theory. This study also contributes to the practical implication that social capital in the form of the strength of relations with external is useful for competitiveness and in maintaining the sustainability of the company.